Renewable Energy Sources vs. an Air Quality Improvement in Urbanized Areas - the Metropolitan Area of Kraków Case - Blazy, Rafał; Błachut, Jakub; Ciepiela, Agnieszka; Łabuz, Rita; Papież, Renata (Frontiers in Energy Research, 2021)
The premise for the selection of the topic discussed in this article is the lack of research on the level of reduction of air pollutant emissions by the use of photovoltaic micro-installations in single-family buildings, both in Poland and other countries of Central and Eastern Europe. Therefore, the authors made an attempt to estimate the scale of air pollution reduction (in particular CO2) in the area of the urbanized Metropolitan area of Krakow, which is one of the most polluted regions in Poland. The installation of photovoltaic panels on single-family buildings, co-financed by the government My Electricity Program, is the investment cost in improving the air quality in this region, and thus increasing the well-being of its inhabitants.